Inborn Errors of Metabolism: From Neonatal Screening to Metabolic Pathways: Book review - Amaral, Olga (2017)
Book Review of ‘Inborn Errors of Metabolism: From Neonatal Screening to Metabolic Pathways’ edited by two well-known specialists in the area of inborn errors of metabolism (IEMs), Brendan Lee and Fernando Scaglia, gives us a different vision in this field.